Sperm competition in tropical versus temperate zone birds - Albrecht, Tomáš; Kleven, Oddmund; Kreisinger, Jakub; Laskemoen, Terje; Omotoriogun, Taiwo C; Ottosson, Ulf; Reif, Jiří; Sedláček, Ondřej; Hořák, David; Robertson, Raleigh J; Lifjeld, Jan T (Proceedings. Biological sciences, 2013)
Sperm competition represents an important component of post-copulatory sexual selection. It has been argued that the level of sperm competition declines in birds towards the equator. However, to date, sperm competition estimates have been available mainly for avian species inhabiting the northern temperate zone. Here we apply a novel approach, using the coefficient of between-male variation (CV(bm)) in sperm size as an index for sperm competition risk, in a comparative analysis of 31 Afrotropical and 99 northern temperate zone passerine species. We found no difference in sperm competition risk between the two groups, nor any relationship with migration distance. However, a multivariate model indicated that sperm competition risk was highest in species with a combination of low body mass and few eggs per clutch. The effect of clutch size was most pronounced in tropical species, which indicates that sperm competition risk in tropical and temperate species is differently associated with particular life-history traits. Although tropical species had lower sperm competition risk than temperate zone species for overlapping clutch sizes, the idea of a generally reduced risk of sperm competition in tropical birds was not supported by our analysis.
Keywords: migrace zvířat; roční období; sexuální chování zvířat; Passeriformes; Female; velikost těla; Clutch Size; Ecosystem; Body Size; Multivariate Analysis; multivariační analýza; Spermatozoa; velikost snůšky; Seasons; ekosystém; mužské pohlaví; spermie; Animal Migration; zvířata; ženské pohlaví; Animals; Male; Sexual Behavior, Animal